Megaciudades, globalización y viabilidad urbana - Boris Graizbord (Investigaciones Geográficas, 2007)
At the end of the twentieth century there were hundreds of cities of one million inhabitants or more. In 1990 there were only a dozen of these. Growth and demographic concentration on these kind of urban agglomerations will continue mainly in the developing countries during the present century. It is expected that three out of four from the 4 000 million new inhabitants in the world will settle in Asia, Africa and Latin America in the next half century.In this paper a description of the world distribution of these cities is presented. A reference is made to the case of Mexico and the growth of megacities and the factors explaining it follows. The text ends with some thoughts about the urban and environmental policy implications that these cities will have in developing countries and in Mexico in particular.